Fulfillment of the Rights of Persons with Disabilities in Yogyakarta Under DIY Regional Regulation No. 4 of 2012 - Amalia Azahra; Ninuk Wijiningsih (JUSTISI, 2026)
This study aims to analyze the conformity between the Regional Regulation of the Special Region of Yogyakarta Number 4 of 2012 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities and Law Number 8 of 2016 concerning Persons with Disabilities, as well as to examine the implementation of the rights fulfillment of persons with physical disabilities by the Yogyakarta City Government. This research employs a normative legal method using statutory and conceptual approaches, supported by primary data obtained through interviews with officials of the Yogyakarta City Social Service Office. The collected data were analyzed qualitatively using deductive reasoning. The novelty of this study lies in its comprehensive assessment of not only the harmonization of national and regional legal frameworks but also the effectiveness of policy implementation through the role of local government in fulfilling the rights of persons with physical disabilities. The findings reveal that Regional Regulation Number 4 of 2012 is substantially aligned with Law Number 8 of 2016 in guaranteeing rights related to education, healthcare, employment, accessibility, and public services. However, its implementation remains suboptimal due to limited accessibility facilities, inadequate supervision, inaccurate disability data, and persistent social stigma. This study concludes that while normative legal conformity has been achieved, the effective fulfillment of the rights of persons with physical disabilities requires stronger oversight, improved accessibility, and more inclusive policy implementation.